Comparison of the Effectiveness of Three Educational Methods (E-Learning, Lectures and Blended) on Pharmacy Students' Knowledge of Non-prescription Drugs - Kouti, Leila; Aghsam, Zahra; Sayyah Bargard, Mehdi; Javadi, Mohammad Reza; Aghakouchakzadeh, Maryam; Eslami, Kaveh (Pharmacy Education, 2018)
Introduction: Non-prescription medications are increasingly used all over the world and therefore pharmacists should be able to counsel the patients on their proper uses and safety. Pharmacy students take courses in this area and given its importance; teaching innovations and different methods are used by schools and institutions. The present study was designed to compare the effectiveness of different delivery methods of the knowledge of non-prescription drugs. Methods This interventional study was conducted with pharmacy students of University of Medical Sciences in the year of 2015-16. In this study, topics were divided into three groups, (lecture-based, electronic teaching and blended approach). At the beginning and end of each session, pre and post-tests were performed and the students took a final exam at the end of the semester. The mean difference of the final exam scores of topics taught by each method was compared. Also, the possible improvements of the students' posttest scores compared to their pre-tests were analyzed. Results The Students' final exam mean scores were 16.166±0.332 in e-learning group, 13.751±0.164 in lecture group and 16.388±0.195 in blended methods group (all out of 20 points). The results show that the e-learning and blended methods had a more positive effect on the scores of the final exam of pharmacy students in knowledge of non-prescription medication course. Conclusion This study demonstrates that a blended learning method and an e-learning approach can positively influence the student’s knowledge towards non-prescription drugs.